Intermixing‐Driven Surface and Bulk Ferromagnetism in the Quantum Anomalous Hall Candidate MnBi6Te10. Issue 10 (17th February 2023) - Tcakaev, Abdul‐Vakhab; Rubrecht, Bastian; Facio, Jorge I.; Zabolotnyy, Volodymyr B.; Corredor, Laura T.; Folkers, Laura C.; Kochetkova, Ekaterina; Peixoto, Thiago R. F.; Kagerer, Philipp; Heinze, Simon; Bentmann, Hendrik; Green, Robert J.; et al.
Abstract: The recent realizations of the quantum anomalous Hall effect (QAHE) in MnBi2 Te4 and MnBi4 Te7 benchmark the (MnBi2 Te4 )(Bi2 Te3 ) n family as a promising hotbed for further QAHE improvements. The family owes its potential to its ferromagnetically (FM) ordered MnBi2 Te4 septuple layers (SLs). However, the QAHE realization is complicated in MnBi2 Te4 and MnBi4 Te7 due to the substantial antiferromagnetic (AFM) coupling between the SLs. An FM state, advantageous for the QAHE, can be stabilized by interlacing the SLs with an increasing number n of Bi2 Te3 quintuple layers (QLs). However, the mechanisms driving the FM state and the number of necessary QLs are not understood, and the surface magnetism remains obscure. Here, robust FM properties in MnBi6 Te10 ( n = 2) with T c ≈ 12 K are demonstrated and their origin is established in the Mn/Bi intermixing phenomenon by a combined experimental and theoretical study. The measurements reveal a magnetically intact surface with a large magnetic moment, and with FM properties similar to the bulk. This investigation thus consolidates the MnBi6 Te10 system as perspective for the QAHE at elevated temperatures. Abstract : Stabilizing the quantum anomalous Hall effect in a magnetic topological insulator such as MnBi6 Te10 is a promising route toward topological qubits, ultra‐low‐power electronics and spintronics. The most fundamental ingredient is ferromagnetic order; however, in pristine MnBi6 Te10, the consecutive Mn layers interact antiferromagnetically. Here, it is demonstrated how Mn and Bi intermixing between their respective atomic positions may induce robust ferromagnetism.